Charlie and the Chocolate Factory - Dahl, Roald; Blake, Quentin (London: Puffin Books, Uk, 2001)
Each of five children lucky enough to discover an entry ticket into Mr. Willy Wonka's mysterious chocolate factory takes advantage of the situation in his own way.
Originally published: London : Puffin Books, 1998.
Keywords: Wonka, Willy (Fictitious character); Chocolate factories -- Juvenile fiction; (Fictitious character) -- Juvenile fiction